High acceptability of rapid HIV self-testing among a diverse sample of MSM from Buenos Aires, Argentina - Pando, María de los Ángeles (2017)
The objective of this study was to explore the acceptability of rapid HIV self-testing (RHST)among men who have sex with men (MSM).MethodsDuring 2006±2009, a sample of 500 MSM was recruited through Respondent Driven Samplingfor an HIV prevalence/incidence study. Attitude toward RHST was explored amongHIV negative MSM. Data were weighted prior to analyses.ResultsParticipants reported they were likely to buy RHST (74%), test themselves more frequentlythan they currently do (77%), and that the procedure would simplify testing (70%). Furthermore,71% reported they would probably use it alone, 66% would use it with a steady partner,and 56% with a friend/partner. While a majority acknowledged that RHST use woulddeprive them of receiving counseling (61%), 74% declared they would go for help if theytested positive; 57% would use an RHST in order to avoid condoms. Probability of use surpassed70% among gay and non-gay identified MSM as well as those with and without aprevious HIV test. Those likely to buy RHST were older (p = 0.025) and more likely to identifyas gay (p = 0.036). A total of 17% said they would think about killing themselves and 9%would attempt suicide if they tested positive. These MSM were more likely to be younger(p<0.001), with lower mood level (p<0.001) and greater feelings of loneliness (p = 0.026).ConclusionsThe high acceptability of RHST found among MSM should encourage the authorities to considerthe possibility of offering it for self-testing, as it can improve early diagnosis and preventionof future transmissions. However, further research is needed to understand how to best disseminate RHST among MSM who wish to use it and to offer support and linkage tocare for those who test HIV-positive.